2007
DOI: 10.1016/j.jvs.2006.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Suprarenal fixation of endovascular aortic stent grafts: Assessment of medium-term to long-term renal function by analysis of juxtarenal stent morphology

Abstract: RAO coverage by suprarenal uncovered stents does not appear to have a significant effect on renal function as evaluated by creatinine measurements in patients with normal preoperative renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 39 publications
0
34
1
Order By: Relevance
“…To date, several observational studies have reported the efficacy and safety of suprarenal endograft fixation. [280][281][282][283][284] Moreover, almost 50% and 87% of endografts used in the DREAM and EVAR-1 trials, respectively, were performed with endografts that used suprarenal fixation. Significantly, rates of renal dysfunction appear to be equivalent for endografts with transrenal nitinol or stainless steel stents and not significantly different among patients undergoing EVAR with infrarenal or suprarenal fixation.…”
Section: Endovascular Repairmentioning
confidence: 99%
“…To date, several observational studies have reported the efficacy and safety of suprarenal endograft fixation. [280][281][282][283][284] Moreover, almost 50% and 87% of endografts used in the DREAM and EVAR-1 trials, respectively, were performed with endografts that used suprarenal fixation. Significantly, rates of renal dysfunction appear to be equivalent for endografts with transrenal nitinol or stainless steel stents and not significantly different among patients undergoing EVAR with infrarenal or suprarenal fixation.…”
Section: Endovascular Repairmentioning
confidence: 99%
“…Despite initial concerns about suprarenal stent struts impinging the renal ostium, the risk of embolization, 59 or peri-strut neointimal hyperplasia, 60 we, like previous authors, 61 successfully used suprarenal fixation without any adverse effects on renal function even after 4 years' follow-up. 17 Leurs et al 62 have analyzed the EUROSTAR registry data and reported that neck lengths ,15 mm predispose to increased risk of short-and midterm proximal endoleaks post EVAR.…”
Section: ¤ ¤mentioning
confidence: 80%
“…Because there is no fabric attached to the stent, the mesenteric and renal arteries remain perfused, although concerns have been raised regarding the potential risks of embolization to or occlusion of the renal and/or mesenteric arteries by the suprarenal components (20). Several studies have reported the safety and efficacy of suprarenal fixation (21)(22)(23)(24)(25), with similar rates of renal dysfunction in EVAR performed with suprarenal and infrarenal fixation (24). However, there are reports of renal infarction and renal artery occlusions in patients with preexisting renal arterial disease (26,27), as well as of visceral compromise and arterial occlusion (28,29) with the use of suprarenal fixation.…”
Section: Endovascular Aneurysm Repairmentioning
confidence: 99%